CLIMATIC TOURISM MOTIVES AND THEIR ROLE IN SPATIAL ORGANIZATION AND TOURISM DEVELOPMENT OF THE NORTH-EASTERN REGION OF BOSNIA - Nezirović, Senada (International Journal of Research -GRANTHAALAYAH, 2018)
The climate of the north-eastern Bosnia belongs to the moderate continental type, where there are certain specifics caused by relief, geographic position, proximity to the Pannonian basin, mountain central massif and the distance from the Adriatic Sea. The area of northeastern Bosnia has similar climate characteristics as well as the countries of Central Europe: warm summers, cold winters, chilly autumn and rainy spirng. The climate of northeastern Bosnia is influenced by a series of factors that determine all of its elements: air temperature, humidity, air pressure and sunshine duration. This paper analyzes the basic climatic elements of the Northeastern Bosnia region. During the field research, the emphasis was placed on climate tourism motives and their role in spatial organization and development of tourism. On the basis of a shorter analysis, we tried to distinguish tourist areas and facilities with the dominant function of tourism, in which tourism can become a dominant economic activity.